2016
DOI: 10.1186/s12868-015-0236-5
|View full text |Cite
|
Sign up to set email alerts
|

SP, CGRP changes in pyridoxine induced neuropathic dogs with nerve growth factor gene therapy

Abstract: BackgroundNerve growth factor (NGF) is known not only as a major factor for neuronal plasticity but also as a pain stimulator. Although there have been several trials with NGF for its application in the regeneration or protection of the nervous system, the pain induced by NGF remains a challenge to be overcome. In this study, the pain induced by NGF gene therapy was evaluated.ResultsVehicle or recombinant dog NGF plasmid was administered into the intrathecal space of dogs. Twenty-four hours after the vehicle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 46 publications
4
37
0
Order By: Relevance
“…Taken together, the results from the current study support other findings from our laboratory [ 8 10 ] and suggest that polyarginine and arginine-rich peptides may represent a new class of neuroprotective agents with enormous clinical potential for the treatment of acute and chronic neurological injuries. Importantly, it is possible that the reported beneficial effects of arginine-rich cell penetrating peptides fused to a “neuroprotective peptide” in animal studies of acute brain injury are largely attributable to the effects of the arginine residues contained within the peptide [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Taken together, the results from the current study support other findings from our laboratory [ 8 10 ] and suggest that polyarginine and arginine-rich peptides may represent a new class of neuroprotective agents with enormous clinical potential for the treatment of acute and chronic neurological injuries. Importantly, it is possible that the reported beneficial effects of arginine-rich cell penetrating peptides fused to a “neuroprotective peptide” in animal studies of acute brain injury are largely attributable to the effects of the arginine residues contained within the peptide [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present study add to our previous findings, which showed that 1000 nmol/kg R18 when administered 30 minutes after permanent MCAO significantly reduces infarct volume in the rat [ 10 ]. Importantly, we now show that R18 is effective over an even wider therapeutic window (60 min) and broader dose range (100–1000 nmol/kg) and that, on balance, R18 is more effective than the extensively characterised neuroprotective peptide, TAT-NR2B9c.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…PNI extending into the extrapancreatic nerve plexus is a histopathological characteristic of PC and leads to abdominal pain 6. NGF induces thermal and mechanical sensitization of neurons, and the recent use of NGF-sequestering antibodies attests to the ongoing role of this neurotrophin in chronic pain 23 24. However, the specific mechanism contributing to PC pain is unclear.…”
Section: Discussionmentioning
confidence: 99%